Analysis of amino acid enantiomers from aged fingerprints. Issue 15 (30th March 2020) - van Helmond, Ward; Weening, Maarten; Vleer, Vonne; de Puit, Marcel
Abstract : The use of the enantiomeric ratio of D/L-serine in fingerprints could pose as interesting target for age estimation techniques. Abstract : Fingerprints found at a crime scene can be key in criminal investigations. A method to accurately determine the age of the fingerprint, potentially crucial to linking the fingerprint to the crime, is not available at the moment. In this paper, we show that the use of the enantiomeric ratio of d /l -serine in fingerprints could pose as interesting target for age estimation techniques. We developed a UPLC-MS/MS method to determine the enantiomer ratios of histidine, serine, threonine, alanine, proline, methionine and valine from fingerprint residue. We found a significant change only in the relative ratio of d -serine with increasing fingerprint age after analysis of fingerprints up to 6 months old.